c-Met Inhibitor Synergizes with Tumor Necrosis Factor–Related Apoptosis-Induced Ligand to Induce Papillary Thyroid Carcinoma Cell Death - Bu, Rong (ScholarOne, 2011)
The Met receptor tyrosine kinase is overexpressed and/or activated in variety of human malignancies. Previously we have shown that c-Met is overexpressed in Middle Eastern papillary thyroid carcinoma (PTC) and significantly associated with an aggressive phenotype, but its role has not been fully elucidated in PTC. The aim of this study was to determine the functional link between the c-Met/AKT signaling pathway and death receptor 5 (DR5) in a large cohort of PTC in a tissue microarray format followed by functional studies using PTC cell lines and nude mice. Our data showed that high expressions of p-Met and DR5 were significantly associated with an aggressive phenotype of PTC and correlated with BRAF mutation. Treatment of PTC cell lines with PHA665752, an inhibitor of c-Met tyrosine kinase, inhibited cell proliferation and induced apoptosis via the mitochondrial pathway in PTC cell lines. PHA665752 treatment or expression of c-Met small interfering (si)RNA resulted in dephosphorylation of c-Met, AKT and its downstream effector molecules. Furthermore, PHA665752 treatment upregulated DR5 expression via generation of reactive oxygen species in PTC cell lines, and synergistically potentiated death receptor–induced apoptosis with tumor necrosis factor–related apoptosis-inducing ligand (TRAIL). Finally, cotreatment with PHA665752 and TRAIL caused more pronounced effects on PTC xenograft tumor growth in nude mice. Our data suggest that the c-Met/AKT pathway may be a potential target for therapeutic intervention for treatment of PTC refractory to conventionally therapeutic modalities.